Cryo-EM reveals integrin-mediated TGF-β activation without release from latent TGF-β - Campbell, Melody G. (Cell, 2020)
Integrin αvβ8 binds with exquisite specificity to latent transforming growth factor-b (L-TGF-β). This binding is essential for activating L-TGF-β presented by a variety of cell types. Inhibiting αvβ8-mediated TGF-β activation blocks immunosuppressive regulatory T-cell differentiation, which is a potential therapeutic strategy in cancer. Using cryo-electron microscopy, structure-guided mutagenesis, and cell-based assays, we reveal the binding interactions between the entire αvβ8 ectodomain and its intact natural ligand, L-TGF-β, as well as two different inhibitory antibody fragments to understand the structural underpinnings of αvβ8 binding specificity and TGF-β activation. Our studies reveal a mechanism of TGF-β activation where mature TGF-β signals within the confines of L-TGF-β and the release and diffusion of TGF-β is not required. The structural details of this mechanism provide a rational basis for therapeutic strategies to inhibit αvβ8-mediated L-TGF-β activation.